Report on the 26th Polish Scientific Conference “Philosophy of Sustainable Development” (Warsaw, 15 March 2023) - Klimska, Agnieszka (Studia Ecologiae et Bioethicae, 2023)
The 26th National Scientific Conference “Philosophy of Sustainable Development” was held on 15 March 2023 in Warsaw and was organised by the Department of Ecophilosophy at Cardinal Stefan Wyszyński University. The gathering brought together speakers from various academic institutions, who delivered presentations ranging from philosophical foundations and pedagogical frameworks to practical environmental protection measures. Plenary sessions addressed the outlook on a potential global catastrophe, the ethics of recycling, and consumer moderation, while two parallel tracks focused on education for sustainable development and interdisciplinary natural and technical science research. In total, nineteen papers were presented, with attendees representing universities, government bodies, NGOs, the business sector, and students.